Askola (Ephemeroptera: Leptophlebiidae): Association of Nymph of One Species and Evidence of Cryptic Species Using Molecular Tools - Campos, Rogério; Almeida, Lucas H. [UNESP]; Bispo, Pitágoras C. [UNESP] (Springer Nature, 2025)
Here, we studied Askola specimens sampled from streams in the Caatinga and Atlantic Forest ecoregions of Brazil. We associate nymphs and adults of A. mucuge using molecular tools (COI sequences). The nymph of this species can be differentiated from the two other known nymphs of the genus by the internal denticle medially located at the external incisor of the left mandible and by abdominal terga without marks. In addition, Automatic Barcode Gap Discovery revealed the possibility of cryptic species under the name of Askola froehlichi, suggesting three independent lineages. Our results reduce the Haeckelian and Linnean shortfalls for Askola, since we describe the third nymph of the genus and shed light on the possibility that the most widely distributed Askola species includes putative cryptic species.